Diagnostic Utility of Galectin-3 in Papillary Lesions of Thyroid - Dwarampudi, Raga Sruthi; B.R., Yelikar; Vallabha, Tejaswini; D, Rodrigues Lynda (Annals of Pathology and Laboratory Medicine, 2022)
Introduction: Papillary thyroid carcinoma (PTC) is the most common malignant neoplasm of the neck. Most cases of PTC are diagnosed based on pathologic criteria. However, few thyroid lesions that mimic nuclear features or the architecture of PTC pose diagnostic problems. Papillary projections may be encountered in benign papillary hyperplasia of multinodular goiter, Hashimoto’s thyroiditis, and Graves’ disease. For this reason, the approach to these challenging lesions should include immunohistochemistry. Galectin-3(Gal-3) is an immunohistochemical marker that shows positivity in PTC. The present study was undertaken to investigate whether strong galectin-3 expression is an essential hallmark of PTC or papillary thyroid hyperplasia. Material and Methods: Gal-3 expression was sought by immunohistochemistry in 33 cases of papillary patterns (on microscopy) of thyroid specimens received at our institution. The results obtained were statistically analysed. Result and Conclusion: Of the 33 cases studied, 17 were PTC, and 16 were papillary hyperplasia. Immunohistochemical stain with Galectin -3 revealed a statistically significant P – value, which proves the tendency for Galectin -3 expression is higher in PTC than in papillary hyperplasia.